Adaptation of Lampung Families in Reconstructing 21st Century Skills Implementation During Pandemic - Andi Windah; Purwanto Putra; Ifaty Fadliliana Sari; Vina Karmilasari; Renti Oktaria (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The government’s policy of Learning From Home (LFH) during pandemic emphasizes the importance of 21st Century Literacy Skills due to the ability needed to access media, information and technology. The urgency to increase family adaptive behavior appears as a demanding condition whilst the literacy skills also oppose great challenges for parents as students companions. This study is a cross-sectional survey with quantitative data collection, through questionnaires for 123 respondents at State Elementary School 3 Rajabasa, Bandar Lampung City. Data analysis is done by descriptively and inferentially method. The survey results showed that 87.8% of respondents have facilities to support online access to information. It is also found that the 21 st Century Literacy Skills are mandatory capital owned by each family during LFH activities. The family adaptive abilities in supporting children 21st century literacy skills implementation can be seen through the literacy skills of the students’ families.